Genetic improvement and related activities. Evaluation in uniform nurseries - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The 3-stage progeny evaluation program at CIAT tested 1902 materials (67.4 percent new entries) in 1986, distributed as follows: 1st stage (bean evaluation nursery-VEF), 1282 entries; 2nd stage (preliminary trials-EP), 435 entries; and 3rd stage (IBYAN), 185 entries. The following data are included in table form for these 3 uniform nurseries: no. of sets of international nurseries (VEF-EP-IBYAN) dispatched during 1986 to different countries; no. of bean entries in the 1986 VEF with resistant and intermediate reaction to rust, anthracnose, angular leaf spot, common bacterial blight, and a necrotic and mottled reaction to BCMV; no. of bean entries in the 1986 VEF within each group according to growth habit and maturity; yield and main characteristics of some outstanding lines in the 1986 VEF; av. yield of the bush lines tested in Palmira and Popayan, Colombia (1986 EP); av. yield of the climbing large-seeded lines for cool climates tested in Rio Negro, Colombia (1986 EP); yield of the most outstanding bush lines in the 1986 IBYAN evaluated in Palmira and Popayan. (CIAT)